Use of wire mesh-epoxy composite for strengthening concrete beams /Ismail M. I. Qeshta - Ismail, M. I. Qeshta (2014)
A number of techniques and materials have been proposed for strengthening reinforced concrete (RC) structures. However, the main concern of civil engineers and researchers is to develop an optimum strengthening scheme with materials that are cost effective, durable, and that behave satisfactorily. This study aims to investigate the effectiveness of using a wire mesh-epoxy composite for strengthening concrete beams. This composite consists of wire mesh layers and epoxy resin. In the first step of this study, plain concrete beams were bonded with a different number of wire mesh layers and epoxy resin. As a comparison, the concrete beams were also bonded with a carbon fibre sheet as well as a hybrid of wire meshepoxy and carbon fibre. The test results show that the use of wire mesh with epoxy is an efficient way to improve the flexural performance of concrete beam specimens. The increase in wire mesh layers significantly enhances the flexural strength, cracking behaviour and energy absorption capability. Using four layers of wire mesh was found to be optimum in the composite. In comparison with carbon fibre, wire mesh-epoxy composite is more efficient in flexural strength and ductility. In addition, it was found that a concrete beam bonded with a hybrid wire mesh-epoxy-carbon fibre composite has significantly more energy absorption capability compared to specimens bonded with only carbon fibre. A study on the effect of different configurations of wire mesh-epoxy composite (different wire mesh-epoxy widths) on the flexural behaviour of concrete beams also showed that the wire mesh-epoxy composite for all types of configuration increases the flexural strength. However, the increase in energy absorption of the bonded beams was remarkable. In addition, specimens with large composite width showed better behaviour with respect to the energy absorption capability.The flexural behaviour of RC beams strengthened with wire mesh-epoxy composite was also investigated in this study and was compared with RC beams strengthened with a carbon fibre sheet. In addition, the structural performance of a beam strengthened using a hybrid of wire mesh-epoxy and carbon fibre sheet was investigated. The results showed that the use of wire mesh-epoxy composite provides considerable enhancement in the performance of the strengthened beams. Compared to carbon fibre, the strengthened beams showed more improvement in the first crack load, stiffness and yield strength. In addition, the use of hybrid wire mesh-epoxy-carbon fibre composite indicated better post-yield behaviour and prevented the debonding of the carbon fibre sheet. In general, it can be concluded that wire mesh-epoxy composite could be a new material for the strengthening and retrofitting purposes.